Public health sector workforce in Serbia and world economic crisis - Gajić-Stevanović Milena; Perišić-Rainicke Darinka; Dimitrijević Snežana; Teodorović Nevenka; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2012)
Introduction. Health care, as one of the most important and sensitive fields of human endeavour, has a significant social impact; therefore changes in this area have wide implications on society in general. The latest economic crisis resulted in slow growth of gross domestic product (GDP), high unemployment rates, low living standards, and increased poverty across the globe. This includes decreased capacity of health system, and reduced quality and supply of health services. The aim of the study was to explore possible impact of the current world economic crisis on the public health sector workforce in Serbia. Materials and Methods. The study was conducted as retrospective analyses of the Public Health Institute (PHI) human resource data, the Republic Statistical Office publications and database, the Republic Development Bureau report, as well as the analysis of healthcare expenditures obtained from the Chamber of Health Institutions reports. The comparative analytical method was used for the assessment of socio-economic and human resource indicators over the period of five years, 2006 to 2010. Results. Results showed that the world economic crisis discontinued steady economic growth in Serbia. Between 2006 and 2008, the real GDP growth rate has been fluctuating between 3.6% and 5.4 %, while in 2009 it had negative growth rate of -3.1 % and slight increase in 2010 of 1.0%. In 2006, the GDP per capita was US$ 3,943, and by 2008 it almost doubled reaching US$ 6,498, while in 2009 it fell down to US$ 5,499, and continued decrease in 2010 to US$ 5,006. In 2007, the overall inflation rate was 6.5%, and after fluctuaion between 11.7% in 2008 and 8.4% in 2009 it droped again to 6.5% in 2010. According to the PHI, from 2006 to 2008 there was steady increase of full-time employees in the public health care sector; from 108,975 in 2006 to 114,317 in 2008. In 2009, the number of full-time employees slightly declined to 114,175 and 114,432 in 2010. There was constant increase in total number of employees in the public health care sector, from 125,081 in 2006 to 129,357 in 2008. In 2009, the total number of employees decreased to 128,694 and in 2010 to 122,695. At the same time, the total expenditure of human resources in the health sector as the percentage of total health expenditure declined from 37.7% in 2006 to 34.7% in 2010. The public health sector salaries after steady increase from 59.9% of total health expenditure in 2006 to 61.2% in 2007 and 2008, decreased to 56.2% in 2010. The unemployment rate for medical doctors almost doubled in 2010 as compared to 2006. Conclusion. Preliminary study results showed that the world economic crisis had negative impact not only on GDP growth rate, the inflation and unemployment rate, but on the public health sector workforce, their salaries and unemployment rate in Serbia.